Nilai Pluralisme Buddhayana Di Indonesia: Merajut Harmoni dalam Keanekaragaman Masyarakat Buddha - Renaldi, Dicky; Sembiring, Denisa Br; Wartini, Sri; Sura Pratama, Arya; Susanto, Susanto (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This research aims to explore the concept offered by Buddhayana regarding pluralism and the implications of the Buddhayana concept of pluralism for the relations between internal sects of Buddhism and other religions. Pluralism is an idea or method that recognizes and appreciates diversity within a community or country. This means recognizing that there are different viewpoints, values, beliefs, and cultures that can exist within it. Pluralism seeks to encourage tolerance, respect differences, and promote cooperation between diverse groups. This research uses library research and interviews which focus on figures from the Buddhayana Council as primary data, as well as related books as secondary data sources. The approach used is a sociological approach, which includes the concept of institutional structure as a conceptual tool. Its function is to integrate relationships and interactions within a social community. The concept of pluralism offered in Buddhayana values in dealing with the issue of plurality is the concept of active harmony. Namely the concept of coexistence with stronger associations and mutual appropriation from various traditions, schools of thought and sects in Buddhism. With the aim of showing the importance of avoiding grouping, sectarianism and forms of division